Pengaruh Model Pembelajaran Kelompok Terhadap Kemampuan Kognitif Siswa di PAUDQU Al Fattah - Evi Puspita; Naely Kamilatul A; Imas Masitoh (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
Basically, children will be very happy when studying in groups according to the friends they want, but sometimes it doesn't last long because there is a mismatch or other things that cause this group learning to be less effective, which in the end students choose to learn individually or some choose to play. Classroom learning is also less diverse so that it makes students feel bored and bored and learning is less fun so students are not interested in what the teacher is saying. This study aims to determine whether or not the influence of the group learning model on students' cognitive abilities in alfatah. The formulation of the problem in this study is whether there is an effect between the implementation of the group learning model on children's cognitive abilities. While the method of this research is the observation of students at PAUDQU Alfattah.